Réponses

2014-05-08T11:18:06+02:00
Bonjour ,
Résoudre les équations :

a) -3(2x -5) = 1 -5x
     -6x +15 =1 - 5x
    -6x +5x = 1 - 15
     -x = -14
      x=14

b) 4-7(2-x) = 5 -4x
    4 - 14 +7x = 5 - 4x
    7x+4x= 5 +14 - 4
    11x = 15
       x= 15/11


c) 5(3 -2x) = (4x +1)
15 -10x = 4x +1
-10x -4x = 1-15
-14x = -14
   x= -14/-14
    x= 1

d) -2(3 + x) + 2x = 6(x +2)
-6 -2x +2x = 6x +12
-6= 6x +12
-6x = 12 +6
-6x = 18
x= 18/ -6
x= - 3
2014-05-08T11:29:04+02:00

a) -3(2x -5) = 1 -5x
-6x +15 =1 - 5x
-6x +5x = 1 - 15
-x = -14
 x=14

b) 4-7(2-x) = 5 -4x
4 - 14 +7x = 5 - 4x
7x+4x= 5 +14 - 4                                                                                                          11x = 15
x= 15/11


c) 5(3 -2x) = (4x +1)
15 -10x = 4x +1
-10x -4x = 1-15
-14x-14                                                                                                                             x= -14/-14
x= 1

d) -2(3 + x) + 2x = 6(x +2)
-6 -2x +2x = 6x +12
-6= 6x +12
-6x = 12 +6
-6x = 18
x= 18/ -6
x= - 3